Design, synthesis, and anti-inflammatory potential of PROTAC drug molecules based on fondaparinux sodium - Wu, Ruoxuan; Zhang, Tianji; Zhao, Siran; Maccarana, Marco; Li, Jin-Ping; Li, Chao; Cao, Hui (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionIn this study, we used an approach by conjugating Fondaparinux Sodium (FS) with selected drugs to generate proteolysis-targeting chimeras (PROTACs).MethodsBy applying bioprocess engineering principles, the direct amidation reaction was optimized –through precise control of pH, substrate ratios, and solvent selection –to reliably produce high‐purity (>99%) PROTAC molecules on a scalable platform. Surface plasmon resonance (SPR) analysis demonstrated that the synthesized PROTACs exhibit micromolar binding affinities (KD ≈ 10–6 M) toward inflammatory mediators RANTES (CCL5) and interleukin-6 (IL-6). In vitro assays using peripheral blood mononuclear cells (PBMCs) revealed that two candidate compounds (Product 6 and Product 10) significantly inhibited lipopolysaccharide (LPS)‐induced interleukin‐1β (IL‐1β) release in a concentration-dependent manner, while FS and the drugs alone had no effect.ResultsHigh-purity (>99%) PROTAC molecules were produced on a scalable platform. The synthesized PROTACs demonstrated micromolar binding affinities (KD ≈ 10–6 M) toward RANTES (CCL5) and IL-6. Two candidate compounds (Product 6 and Product 10) significantly inhibited LPS-induced IL-1β release in PBMCs in a concentration-dependent manner; FS and the drugs alone showed no effect.DiscussionThese findings not only provide an innovative strategy for targeting “undruggable” proteins but also establish a robust, scalable process for the production of PROTAC‐based anti-inflammatory agents.